2015
DOI: 10.1111/jace.13482
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Control of Structural Changes in GeO2 Glass Induced by Femtosecond Laser Direct Writing

Abstract: We report the structural changes inside germania glass induced by femtosecond laser pulses. Inspection by polarization microscopy and secondary electron microscopy indicate that the periodic nanostructures consist of oxygen defects such as ODCs (oxygen deficient centers) and NBOHCs (nonbridging oxygen hole centers) for laser pulse energy less than 0.2 lJ. However, the glass network was dissociated and O 2 molecules were generated for laser pulse energy greater than 0.4 lJ. Two different structural changes, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…This stood for a long time as the only example of a subwavelength structure in silica glass. Recently, fs laser‐induced nanostructures in other glasses have been reported: firstly, close to SiO 2 (e.g., doped silica), GeO 2 (a glass with an atomic arrangement close to SiO 2 ), TiO 2 ‐containing silicate glasses, and two multicomponent borosilicate glasses (with a few mol% of Na 2 O and Al 2 O 3 , BK7 (Schott), and Borofloat 33 (Schott) or alkali‐free aluminoborosilicate glass). For all of these, a similar nanostructure to the one observed in silica glass was described.…”
Section: Discussionmentioning
confidence: 99%
“…This stood for a long time as the only example of a subwavelength structure in silica glass. Recently, fs laser‐induced nanostructures in other glasses have been reported: firstly, close to SiO 2 (e.g., doped silica), GeO 2 (a glass with an atomic arrangement close to SiO 2 ), TiO 2 ‐containing silicate glasses, and two multicomponent borosilicate glasses (with a few mol% of Na 2 O and Al 2 O 3 , BK7 (Schott), and Borofloat 33 (Schott) or alkali‐free aluminoborosilicate glass). For all of these, a similar nanostructure to the one observed in silica glass was described.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, doping of pure silica glass with Ge, F, and P was demonstrated to affect the threshold for nanograting formation. 16 Recently, evidence for femtosecond laser-induced nanogratings has been observed in glasses other than SiO 2 , including several studies reported nanogratings in GeO 2 glass, [17][18][19] binary titanium silicate glass (ULE, Corning), 20,21 and two multicomponent borosilicate glasses (BK7 and Borofloat 33, Schott). 20,22 Germanium dioxide is formed by a three-dimensional network of [GeO 4 ] tetrahedra with all bridging oxygen atoms, whereas ULE glass also possesses structure similar to pure SiO 2 24 were not revealed using scanning electron microscopy despite the induced retardance was of the same level as in Borofloat 33.…”
mentioning
confidence: 99%
“…Using a focus of the femtosecond pulses as a local heat source in a multicomponent glass, we confirmed that the structural changes are isotropic according to the temperature distribution . While, as opposed to the formation of LIPSS on the various materials, the polarization‐dependent bulk nanogratings were observed only in a relatively simple oxides . Meanwhile, the doping effects in amorphous oxides including radiation‐induced structural changes have been widely investigated.…”
Section: Introductionmentioning
confidence: 56%
“…It is known that the nanogratings consisting of oxygen deficiency defect nanoplanes including the nanopores with the diameter below several tens nm were self‐aligned perpendicular to the laser polarization . Such structures are the origin of the strong refractive index contrast leading to the optical anisotropy . The third one being the change in the oxygen deficiency defect concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation